Codigestion of food waste and real traditional Chinese medicine wastewater in anaerobic membrane bioreactor: Stability mechanism and microbial community dynamics - Yong-Xin Cui; Bao-Shan Xing; Su Li; Zi-Yi Wang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Engineering a robust glucose oxidase: Enhanced thermostability, acid tolerance and catalytic activity drive high-level gluconic acid production - Ying-Zhi Peng; Xin-Cheng Jiang; Jing Li; Yi-Fa Yu; Jia-Yu He; Bing-Yan Xu; Xiang Lv; Qiong-Ying Wu; Shuai You; Jun Wang (Food Chemistry, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

SLC6A8-centered placental molecular signature predicts fetal growth restriction via machine learning and single-cell analysis - Qing Hua; Xiaoyan You; Xujing Yan; Yanping Xin; Dongmei Zhang; Xiaona Tian; Li Li (Reproductive Biology, 2026)

Layer‑resolved core-shell hydrogel for in situ fluorescence monitoring of Hg(II) adsorption and removal - Xiaoya Bi; Lijun Luo; Xin Gao; Zixiang Liao; Yue Ren; Cheng Xu; Libo Li; Tianyan You (Journal of Hazardous Materials, 2026)

Corrigendum to “DNA methylation mediates the association between organochlorine pesticides and MASLD: An epigenome-wide association study with integrated AOP framework” [J Hazard Mater, 507 (2026) 141727] - Yi Guo; Yutong You; Xin Guan; Yu Yin; Zhen Yin; Guorong Zhong; Chengyong Jia; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Journal of Hazardous Materials, 2026)

Stronger actions are needed to advance PM2.5 mitigation and its health benefits under population aging in China: Evidence from China’s Clean Air Actions - Jian Qian; Ruoyu Li; You Zou; Jiayi Chen; Junyu Wang; Sheng Li; Na Yang; Tianyue Han; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; et al. (Journal of Hazardous Materials, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

Advancing the identification of toxic by-products in disinfected water by integrating effect-directed analysis and nontarget screening - Xin Li; Fei Cheng; Junlang Qiu; Yu Ling; Jing You (Journal of Hazardous Materials, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

Shear performance of prefabricated utility tunnel joints considering the effect of connectors - Chao Zhang; Jiao-jiao Chen; Wei-ning Zhong; Xin Li; Chen-chen Sun; You-jun Xu; Xin Han; Jun-yi Gao; Jian-jun Wang; Zhi-qiang Fu (Tunnelling and Underground Space Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

The dual origin of granites from fluid-absent and fluid-fluxed melting of the juvenile lower crust: New constraints from Mo isotopes and phase equilibrium modeling - You-Shan Xia; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Yao Zhou; Zhen-Xin Li; Gang Wen; Lei Qin (Geochimica et Cosmochimica Acta, 2026)

Bio-dissolution of hazardous Cu, As, Sb and Zn from polymetallic tetrahedrite by a moderately thermophilic consortium - Xin Nong; Lin Liu; Yuguang Wang; Yufang Guo; You Li; Qiu Yi; Qiuju Mo; Chenbing Ai (Environmental Research, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Population-specific metabolic pathways shape neurotoxicity: Evidence from human biomonitoring of neonicotinoid insecticides and their metabolites in South China - Zhoubing Huang; Xin Li; Huizhen Li; Ruifen Jiang; Hui Li; Jing You (Environmental Pollution, 2026)

Tailored pore engineering in crystalline COF membranes via trimesoyl chloride cross-linking for high-performance pharmaceutical nanofiltration in water treatment - Hao Wang; Lian You; Jian-wei Jia; Yi Wang; Li-ping Yue; Fan-xin Kong (Chemical Engineering Journal, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Chemical constituents with chemotaxonomic significance from the whole plants of Chloranthus sessilifolius K.F.Wu - Xin-Yu Chen; Meng-Li He; Wan-Wan Yu; Yang Liu; Yong-Ming Luo; Ling-Ying Huang; Zhi-Ping Li; Fang-You Chen (Biochemical Systematics and Ecology, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

A comprehensive flavor evaluation method for drinking water based on flavor rating assessment (FRA) and the flavor wheel, incorporating benchmark referencing and objective weighting - You Lyu; Huan He; Zhen-Ning Luo; Tian-Yang Zhang; Xin-Li Huang; Zhu Peng; Qi Fu; Xin-Bai Jin; Bin Xu (Journal of Water Process Engineering, 2026)

Impacts of nitrogen deposition on N2O emissions from agricultural ecosystems in China based on a biogeochemical model - Xin Li; Bocheng Guo; Chuchu Chen; You Zhao; Meijin Zhu; Yueying Fei; Yahuang Su; Hanyu Zhang; Bobo Wu; Yixuan Zheng; Siwen Wang; Zhiliang Yao (Journal of Cleaner Production, 2026)

Insights into the effects of ultrasound on the structural, aggregation behavior, and functional properties of almond isolate protein: An integrated experimental and molecular dynamics simulation studies - Yu-Hang Jiang; Pi-Miao Huang; Yang-You Li; Yu-Ting Zhao; Yue Zheng; Yu-Xing Zhou; Wei-Gang Xin; Hua-Yi Suo (Food Research International, 2026)

Serum polychlorinated biphenyls and risk of metabolic dysfunction-associated steatotic liver disease: Cross-sectional and prospective analyses from the Dongfeng-Tongji cohort - Yutong You; Yi Guo; Xin Guan; Guorong Zhong; Yu Yin; Zhen Yin; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Chengyong Jia; Xi Wang; et al. (Environmental Pollution, 2026)

Synergistic coupling of micellar confinement and interfacial adsorption for fabricating high-density spherical nickel (II) tricarbohydrazide perchlorate - Jie-xin He; Dong-xu Zhang; Feng-yi Xia; Ri-lige Su; Bo-bo Lu; Jia-ni Xie; Zi-jie Bi; Qian-you Wang; Li Yang (Chemical Engineering Journal, 2026)

Aeration strategy and nitrogen loading for stable partial nitrification coupled with oxygen-permeable membranes: Long-term performance, biofilm characteristics, and microbial succession - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Ling-Hu Li; Xin-Xin Sun; Yu-You Li; Rong Chen (Journal of Water Process Engineering, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

DNA methylation mediates the association between organochlorine pesticides and MASLD: An epigenome-wide association study with integrated AOP framework - Yi Guo; Yutong You; Xin Guan; Yu Yin; Zhen Yin; Guorong Zhong; Chengyong Jia; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Journal of Hazardous Materials, 2026)

Potential role of AHL-mediated quorum sensing in filamentous bulking induced by Sphaerotilus natans in the activated sludge process with low dissolved oxygen - Yi Fu; Wei-Xin Liu; Shao-Yang Liu; You-Peng Chen; Song-Ya Li; Fang Fang; Jin-Song Guo; Peng Yan (Journal of Environmental Chemical Engineering, 2026)

Extreme response scenarios for long-span bridges: Probabilistic generation and interpretable clustering under free-flow and congested traffic - Xuejing Wang; Xin Ruan; Joan R. Casas; Mingyang Zhang; Yaohan Li; Haijun Zhou; You Dong (Engineering Structures, 2026)

Sulfur-modified electrolytic manganese residue catalysts promote surface oxidative complex formation for the degradation of nitroimidazole organic pollutants with high half-wave potentials - Xin Xu; Linling Fang; Xiang Lu; Yang Hu; Xueli Yang; Mengke Li; Yun Liu; Yuehui Chen; Zhimin You; Zhiguo He (Chemical Engineering Journal, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Interfacial confinement surface modification (ICSM): A study on the chemical modification of external surfaces of porous powder - Dapeng Fan; Xin You; Haiqun Qi; Fei Zhao; Xupeng Li (Next Research, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

MdCNGC15B, a cyclic nucleotide-gated channel (CNGC) protein, positively regulates the tolerance to drought and salt stress in apple - Xin-Long Guo; Hong-Liang Li; Xiang Wu; Tian-tian Wang; Yan-yan Guo; Jian-Ping An; Chun-Xiang You (Journal of Plant Physiology, 2026)

A cuticular protein mediates thermal and desiccation tolerance through dual regulation of barrier function and water homeostasis - Haiyin Su; Guilei Hu; Bingwei Chen; Qing Hou; Xin Miao; Mengdi Shen; Hang Xiao; Tianpu Li; Yuanyuan Liu; Shijun You; Gaoke Lei (Journal of Insect Physiology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Migrion: a Migrasome-mediated unit for intercellular viral transmission - Yuxing Huang; Xiaojie Yan; Xing Liu; Congcong Ji; Wenmin Tian; Haohao Tang; Yong Li; Yiling Wen; Peiyao Fan; Hongli Wang; Cankun Xi; Zhongtian Li; et al. (Science Bulletin, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Removal of Per- and Polyfluoroalkyl Substances in a Large-Scale Municipal Wastewater Treatment Plant: Performance, Key Factors, and Modeling - Tie-Qing You; Jia Bao; Yang Liu; Yue Wu; Xin Wang; Li Cui (International Journal of Environmental Research, 2026)

COMPASS: A multi-physics coupling platform for safety analysis of lead-cooled fast reactors - Zinan Huang; Yuxing Liu; You-Peng Zhang; Yunxiang Li; Wenjun Hu; Yuping Zhou; Jian Hong; Runsheng Yang; Xin Su (Annals of Nuclear Energy, 2026)

Effects of landscape fragmentation on floodplain fishes as revealed by species–habitat networks - Chen Zhang; Jorge García‐Girón; Ziyu Yang; Ziyu Liu; Shuxin Li; Wenhui You; Yihao Ge; Xin Gao; Yunzhi Yan (Conservation Biology, 2026)
How species interact with habitat patches is influenced primarily by habitat configuration (e.g., connectivity) and species’ functional traits. As levels of fragmentation increase, identifying the intricate connections between these components is crucial for biodiversity conservation. We used the species–habitat network (SHN) approach to identify the links between fish species and lakes in a highly fragmented floodplain; to determine lakes and fish species that are key to maintaining landscape SHN organization; and to examine the impact of habitat configuration and species functional traits on fish responses to loss of lateral hydrological connectivity (LHC). Low metacommunity functional connectivity, lack of robustness, and high modularity (i.e., strong within group interactions) and nestedness indicated low resistance of fish communities to long‐lasting landscape fragmentation, highlighting the importance of large lakes connected by rivers and fishes that migrate between rivers and lakes to maintaining the SHN organization in floodplain ecosystems. The strong association between maximum body length and fish contribution to this network organization indicated that large fish species are potentially more likely to establish interactions at the landscape scale. Trophic level was the main factor controlling the roles of migrating fishes in SHN organization. Based on species’ interactions with habitat patches, we identified and mapped the sites and species responsible for the main features of the SHN structure. Our approach offers new directions for conserving and restoring fragmented floodplains by integrating LHC and fish functional traits to inform targeted conservation priorities.

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Esculin Alleviated NLRP3 Inflammasome Activation by Inducing PINK1/Parkin-Mediated Mitophagy in Cerebral Ischemia–Reperfusion Injury - Jinyu Lin; Bowen You; Xin Yang; Xue Li; Wenjuan Sun; Zhongyu Xu; Yi Zhang; Xuhui Tong; Shuying Dong (Molecular Neurobiology, 2026)

Analysis of Pollution Characteristics and Identification of Driving Factors in Soils at a Typical Petroleum Refinery - Xin Li; Yantao Jian; Guannan Cui; Peili Shi; Yirong Deng; Minke Xu; Jinjin Wei; Yunfeng Xie; Zhimin You (Bulletin of Environmental Contamination and Toxicology, 2026)

Assessment of trace elements and fluoride pollution with soil quality evaluation under different land use types in southern hilly region of China - Xin Wang; You Li; Manyun Zhang; Chengwen Shen; Hao Li; Minghan Wang; Zeheng Li; Huaqin Xu (Environmental Monitoring and Assessment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Low-temperature soda-ash roasting of ludwigite ore: Scale-up feasibility for magnetite and borax production - Jinxiang You; Xin Zhang; Mingjun Rao; Jun Luo; Zhiwei Peng; Guanghui Li (Journal of Environmental Chemical Engineering, 2025)

Methodological innovation in chiral sensing with machine learning and multi-modal signal integration for tryptophan - Xin Wang; Zhaojiang Yin; Binghui Li; Zhibiao Li; Mei You; Quan Chen; Yiwen Li; Hao Fan; Jing Zhang (Chemical Engineering Journal, 2025)

Photothermal nanomedicine for glioblastoma: From material design to clinical translation challenges - Chan Li; Hui-Zhe Xu; Xue-Yan Cheng; Xin Yu; Zhi-Qiang Gong; Yi-Jiang He; Ling-Xiao Zhao; Zhan-You Wang (Chemical Engineering Journal, 2025)

Sesquiterpenoids and monoterpenoids from the aerial parts of Sarcandra glabra (Thunb.) Nakai - Yang Liu; Jie Chen; Wan-Wan Yu; Yong-Ming Luo; Meng-Li He; Xin-Yu Chen; Fang-You Chen (Biochemical Systematics and Ecology, 2025)

The relationship between the dynamic trajectory of inflammatory markers in VA-ECMO patients and the 28-day survival rate, as well as mediating causal analysis - You Zhou; Zhi Cheng; Liqun Sun; Jiayan Han; Suhui li; Xin Wang; Leiming Xu (Inflammation Research, 2025)

Remote sensing–based estimation of monthly CO2 flux in Three Gorges Reservoir drawdown areas - Shuang Zhang; Xin Long; Lang Liu; Fengwen Wang; Zhaofei Wen; Yang Chen; Zhe Li; Chao Peng; Xiangyu You; Jinxin Yang (Journal of Environmental Management, 2025)

Synergistic effects of pre-harvest drought and shade on flavor and aroma enhancement in fermented tea: Insights into JA/ABA signaling and metabolic regulation - Chenyu Shao; Xinyu Peng; You Li; Ziqi Chen; Xin Li; Rong Xu; Shuqi Qiu; Yuqi Luo; Jie Liu; Jianan Huang; Zhonghua Liu; Li Niu; et al. (Food Chemistry, 2025)

Polystyrene nanoplastics impair endometrial decidualization via cell cycle arrest and JNK-MAPK pathway-mediated oxidative stress in early pregnant mice - Jing-Ai Li; Li-Qing Wang; Qiong-Jun Xu; Xiao-Mei Wu; Xiao-Qing Pang; Jin-Xin He; Qian-Feng Qiao; Huang-Nian You; Yan-Chun Wu; Yong-Jiang Zhou (Food and Chemical Toxicology, 2025)

Complexation-precipitation synthesis of high surface area PbO/rice husk-based activated carbon composites for ultra-long-life lead‑carbon battery anodes - Jiecai Li; Yupeng Wu; Zizhun Wang; Qilong Wang; Zhiqiang Liu; Qinwen You; Xin Ding; Yang Sun; Tangjun Wang; Haibo Lin; Nan Lin (Chemical Engineering Journal, 2025)

m6A deficiency impairs uterine spiral artery remodeling to induce preeclampsia-like symptoms via FGF2 - Sun Liu; Wenqian Chen; Jiaqi Chen; Tianqi Liu; Mingqiang Deng; Linjian Xia; Zengguang Li; Junfang Shi; Yuan Li; You Peng; Qihuan Ren; Ziteng Miao; et al. (Science China Life Sciences, 2025)

Mechanistic insights into water use strategies and heat tolerance of Australian native trees in saline soils: Implications for phytoremediation under climate change - Xi Sun; Jie Li; Mohammad Saberian; Gang Ren; Xin Liu; You Gao (Plant and Soil, 2025)
Aims This study evaluates the water use strategies and physiological resilience of three Australian native tree species in saline soils to assess their potential for phytoremediation under climate change. We hypothesise that species with high water demand and delayed stomatal closure under aridity can enhance soil salinity mitigation through sustained transpiration and groundwater regulation. Methods Continuous sap flow measurements were recorded over 12 months on nine trees (three per species) from three species across three moderately saline sites in Melbourne, Australia. Detailed analyses of morphological traits, sapwood properties, and soil profiles (including texture and water content) were conducted. Diurnal sap flow patterns, peak flow timing, and physiological responses to temperature and vapour pressure deficit (VPD) were evaluated to determine species-specific thresholds for heat and drought tolerance. Results Melaleuca styphelioides exhibited the highest water use, consuming 128% and 97% more water monthly than Lophostemon confertus and Corymbia maculata , respectively. Its peak sap flow occurred later in the day (15:00–17:00), coinciding with sustained stomatal conductance under high VPD (1.9–2.0 kPa) and extreme temperatures (41 °C). Optimal physiological performance for this species occurred at higher temperatures (32.2–33.4 °C) and VPD (1.9–2.0 kPa). Conclusions Melaleuca styphelioides may warrant further investigation as a potential candidate for water management in saline environments, given its higher water consumption and ability to maintain sap flow under elevated temperature and VPD conditions. These findings suggest that additional research, incorporating larger sample sizes and direct measurements of soil salinity changes, would be valuable to evaluate the suitability of this species for phytoremediation applications in aridifying regions.

Soil gas geochemical prospecting for deep mineral exploration: A case study of covered deposits on the southern Tibet Plateau - Gao-Xin Li; You-ye Zheng; Khan Junaid; Xin Chen; Jian-Hui Wu; Feng Gao; De-Cai Lin; Yong Zhang (Applied Geochemistry, 2025)

Protective effect of yak yogurt derived Lactiplantibacillus plantarum DACNJS22 fermented milk on DSS-induced colitis: Insights from in vitro and in vivo studies - Yu-Hang Jiang; Yang-You Li; Wei-Gang Xin; Jia-Jia Song; Chen Wang; Hua-Yi Suo (Food Research International, 2025)

Serum polychlorinated biphenyl levels and risk of incident chronic kidney disease: A prospective study in the Dongfeng-Tongji cohort - Sijie Chai; Yutong You; Yi Guo; Xin Guan; Guorong Zhong; Zhen Yin; Yu Yin; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Environmental Pollution, 2025)

Targeted nutrient addition reduces the trade-offs between ecosystem services in degraded grasslands - Chunhe You; Jixi Gao; Na Lv; Xiaoman Liu; Xin Li (Ecological Engineering, 2025)

Development of a multifunctional and biocompatible hydrogel for flexible implantable sensors - Kaiqi Zhang; Huibiao You; Yuxi Liu; Fulei Lin; Yanan Li; Lina Jia; Jinxiao Bao; Xin Ge; Gaofei Pan; Huitao Yu; Ruiguang Xing (Chemical Engineering Journal, 2025)

Halide anions-facilitated structural manipulation in Mn-based hybrids for multicolor emission and X-ray imaging - Tong Chang; Tongtong Kou; Qilin Wei; Liang Wang; Xiulian Cai; Huanxin Su; Yuanxiang You; Xin Li; Xinxin Han; Shiguo Han; William W. Yu (Chemical Engineering Journal, 2025)

Self-cleaning photocatalytic membranes in oil-water separation: Design strategies and sustainability challenges - Chen Zhao; Pengrui Jin; Qin Chen; Jiale Du; Junwei Li; Xin Xiao; Zhao Yang; Qingqing You; Shushan Yuan; Bart Van der Bruggen (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Discovery of undescribed schinortriterpenoids from Schisandra chinensis by molecular networking and their neuroprotective effects - Peng Jiang; Yu-Meng Luo; Xin-Yuan Li; Shu-Jun Zhang; Wei Guan; Anam-Naseem; Yu-Hang Fan; Qing-Shan Chen; Li-Li Zhang; Hong-Yan Yao; Xiao-Xue He; Hai-Xue Kuang; et al. (Phytochemistry, 2025)

Unveiling the prevalence of metal resistance genes and their associations with antibiotic resistance genes in heavy metal-contaminated rivers - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Hai-Yan Yang; Liang-Ying He; Hong Bai; Feng Liu; Xiao-Wei Jin; Guang-Guo Ying (Water Research, 2025)

Silico-oxygen bonding integrated with nano-size pore enrichment enables sustainable low-oxidant-consumption Fenton-like chemistry - Qingbai Tian; Xin Zhang; Jiale Chang; Dongdong Chen; Siyuan You; Xiaoming Peng; Baoyu Gao; Yanan Shang; Bo Wei; Qian Li; Zhen Hu; Yue Gao; et al. (Water Research, 2025)

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

The R2R3-MYB transcription factor MdMYB62 negatively regulates the drought and salt tolerance in apple - Xin-Long Guo; Xiang Wu; Hong-Liang Li; Ran-Xin Liu; Jian-Ping An; Chun-Xiang You (Journal of Plant Physiology, 2025)

Meroterpenoids with bicyclic polyprenylated acylphloroglucinol scaffold and anti-inflammatory activity from Hypericum lancasteri - Jin-Qiu You; Yun-Qi Jin; Yu-Meng Miao; Xin-Yu Sun; Jia-Yu Yang; Jin-Chang Huang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Effective treatment of Cu2+-containing acid mine drainage with acidic-cupric resistant electroactive biofilms - Jing Song; Xin Nong; You Li; Yifei Liao; Boyu Xu; Wuhao Zhang; Xuan Qin; Lin Liu; Yuguang Wang; Chenbing Ai (Journal of Environmental Management, 2025)

Cytotoxicity phenylpropanoid amides from the seed of Cannabis sativa L - Ao-Fei Wang; Juan Pan; Xiang Liu; Xin-yuan Li; Peng Jiang; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-li Zhang; Hai-Xue Kuang; Yan Liu; Bing-You Yang (Natural Product Research, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Method for planning subarea emission reduction strategies to improve ozone over a large area: A case of Taiwan - Tu-Fu Chen; Xin-Li Gong; Chang-You Tsai; Ken-Hui Chang (Atmospheric Environment, 2025)

Mechanistic analysis of urban tree-soil interactions: Species-specific water use and desiccation effects on expansive clays - Xi Sun; Jie Li; Xin Liu; Shengshen Wu; You Gao (Plant and Soil, 2025)
Aims This study investigates the complex interactions between urban trees and expansive clay soils, focusing on two prevalent species ( Corymbia maculata and Lophostemon confertus ) in Melbourne’s urban landscape. Limited field data and understanding of species-specific water use necessitate this research. We aim to quantify the spatiotemporal variability in soil-plant-water interactions within the urban contexts, a crucial factor for informed green infrastructure planning and sustainable ecosystem management in metropolitan areas. Methods Comprehensive field measurements were conducted over 12 months, including soil movement, soil water dynamics, tree transpiration, and leaf water potential. Sap flow sensors monitored tree water requirements. Laboratory soil testing determined soil properties and developed soil suction and water content profiles. The intercorrelation between soil water dynamics and tree water use was investigated. Results Peak water use for both trees occurred during summer, contributing 32–40% of their total consumption. C. maculata transpired 48.1 kL, exceeding L. confertus by 106%. The trees’ desiccation influence extended horizontally to 0.4–0.5 times the tree height and vertically to 2.3–3.3 m depth. Soil water content explained 31–36% of soil movement variability, with a strong correlation (R² > 0.9) between soil suction and water content within the active root zone. Conclusions This study enhances our mechanistic understanding of urban tree-soil interactions, providing valuable insights for sustainable city planning. It emphasizes species-specific considerations in tree selection and placement, especially in areas with expansive soils. The robust field data contributes to refining predictive models of soil-plant-atmosphere interactions in urban landscapes, supporting informed decision-making in urban greening initiatives.

Fate and transformation of psychotropic drugs in urban wastewater systems and receiving rivers via the integration of targeted and suspect screening analysis - An-Guo Wang; Jin-Na Zhang; Li-Xin Hu; You-Sheng Liu; Guang-Guo Ying; Yin-Xiu Liang; Mei-Ying Xu; Zhi-Qiang Yu (Water Research, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Synergistic protective effects of probiotics Lactiplantibacillus plantarum S58 and prebiotics Qingke β-glucan on dextran sulfate sodium-induced cognitive deficits in colitis mice: A study of microbial-gut-brain axis modulation - Yu-Hang Jiang; Jia-Xin Zhao; Yang-You Li; Wei-Gang Xin; Jia-Jia Song; Xiao-Yong Chen; Chen Wang; Hua-Yi Suo (Food Bioscience, 2025)

Co species modulating of BiOBr-based Z-scheme heterojunction for the transform photoreduction CO2 products from CO to CH4 - Run-Jing You; Kuan Wang; Huan Ma; Xin-Peng Li; Zhe Cao; Zhen-Hong He; Huan Wang; Weitao Wang; Xiaojuan Lai; Zhao-Tie Liu (Chemical Engineering Journal, 2025)

Probiotic potential of intestinal bacteria isolated from the digestive tract of hybrid snakehead (Channa argus♀ × Channa maculata♂) - Wen-Hao Wu; Yan-Xin Sun; Jia-Hao Zhang; Kun-Ming Huang; Xi-Chao Liu; Shu Tang; Wei Li; Biao Jiang; You-Lu Su (Aquaculture, 2025)

Effect of UV-C irradiation treatment on mycotoxins production in Fusarium species inoculated wheat seeds during wheat germination - Yanshen Li; Xinru Li; Xin Mao; Chaofan Yuan; Yanli You; Jiqiang Zhao; Shuang Zhou; Yongning Wu (Food Chemistry, 2025)

Toxicity assessment of wastewater using a battery of bioassays in two textile wastewater treatment plants from a large industrial park in Guangxi, Southwest China - Feng-Jiao Peng; Sen Li; Wen-Dan You; Xin-Yu Wang; Xing-Jun Feng; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Lactiplantibacillus plantarum DACNJS22 alleviates benzo(a)pyrene-induced neurobehavioral injury in mice: Insights from gut microbiota and short-chain fatty acids - Yu-Hang Jiang; Yang-You Li; Wei-Gang Xin; Yu-Ting Zhao; Xiao-Yong Chen; Jia-Jia Song; Chen Wang; Hua-Yi Suo (Food Bioscience, 2025)

Investigating the interaction mechanisms between arachin and resveratrol: Utilizing multi-spectroscopy and computational chemistry - Yu-qi Yang; Qi Gao; Shi-qi Yue; Xue Peng; Ning Wang; Jing-li Xin; Miao Yu; Jia-jia Rao; You-lin Xue (Food Chemistry, 2025)

Onboard measurements of organic vapor emissions from river vessels under various operational conditions - Mengxue Tong; Yanli Zhang; Mei Li; Qi Wang; Xiao Tian; Dan Zhang; Aoqi Ge; Wei Song; Xin Xiong; Yinong You; Yongjang Xu; Yihua Huang; et al. (Environmental Pollution, 2025)

In silico screening of dyes for enhanced silk coloring using the feeding approach - Zhuangwei Zhang; Yucheng You; Shuoqi Jiang; Yuncheng Tang; Zhongwei Jia; Jian-Xin Li (Sustainable Chemistry and Pharmacy, 2024)

Modified biochar affects CO2 and N2O emissions from coastal saline soil by altering soil pH and elemental stoichiometry - Yang Dong; Xin Zhang; Xiao Wang; Chenghao Xie; Jiantao Liu; Yadong Cheng; Yanmin Yue; Xiangwei You; Yiqiang Li (Science of The Total Environment, 2024)

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

Unveiling the overlooked small-sized microbiome in river ecosystems - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Lu-Kai Qiao; Zi-Yin Chen; Jian-Qiang Su; Liang-Ying He; Hong Bai; Yong-Guan Zhu; Guang-Guo Ying (Water Research, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

High electromagnetic wave absorption performance from all-scale hierarchically defective Ni-Mn-Co-Cu-Al high entropy alloys@carbon - Shuangfu Gang; Yongxin Qian; Tianshun Xiong; You Li; Wang Li; Zheng Ma; Wenguang Zhang; Hui Long; Yingchao Wei; Xin Li; Qinghui Jiang; Yubo Luo; et al. (Chemical Engineering Journal, 2024)

Antiallodynic and antihyperalgesic effects of decursin associated with correcting mitochondrial dysfunction and oxidative stress in type 1 diabetic mice - Li Ma; You-Ya Fan; Ben-Ling Li; Feng Xu; Xin Zhao (Chemico-Biological Interactions, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Discovering transformation products of pharmaceuticals in domestic wastewaters and receiving rivers by using non-target screening and machine learning approaches - Yu Han; Li-Xin Hu; Ting Liu; Liang-Li Dong; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2024)

Mitochondrial DNA copy number mediated the associations between perfluoroalkyl substances and breast cancer incidence: A prospective case-cohort study - Yue Feng; Yingqian You; Mengying Li; Xin Guan; Ming Fu; Chenming Wang; Yang Xiao; Meian He; Huan Guo (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

SIMS U-Pb dating of baddeleyite-zircon pairs in mafic rocks to determine the ages of magmatic mineralization and hydrothermal remobilization in a Ni-Cu-(PGE) deposit - Li-Xing Li; Jian-Wei Zi; Yu Liu; Guo-Qiang Tang; Hou-Min Li; Yong Zhang; Min-Xin You (Precambrian Research, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

Non-target discovery and risk prediction of per- and polyfluoroalkyl substances (PFAS) and transformation products in wastewater treatment systems - Ting Liu; Li-Xin Hu; Yu Han; Sheng Xiao; Liang-Li Dong; Yuan-Yuan Yang; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

Inhibition of Extracellular Signal-Regulated Kinase Activity Improves Cognitive Function in Mice Subjected to Myocardial Infarction - Yibo Yin; Xin Li; Xiaoxua Zhang; Xinru Yuan; Xingji You; Jingxiang Wu (Cardiovascular Toxicology, 2024)

OLOD: a new UAV dataset and benchmark for single tiny object tracking - Mengfan Yu; Yulong Duan; You Wan; Xin Lu; Shubin Lyu; Fusheng Li (International Journal of Remote Sensing, 2024)

Evolution of runoff discharge patterns and risk assessment of water inrush in mountainous railroad tunnels - Xu Yang; Dandan You; Xin Gao; Qi Li; Xinhao Hu; Saixing Zeng; Jingxiao Zhang; Yanping Hu; Lanxin Kang (Natural Hazards, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Fourteen undescribed steroidal saponins from Solanum capsicoides leaves and their neuroprotective effects - Yan Liu; Xin-Yuan Li; Jia-tong Wu; Han Wang; Xin Meng; Hai-Dan Zou; Juan Pan; Wei Guan; Adnan Mohammed Algradi; Anam Naseem; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Short-time potentiostatic assisted borate to induce the generation of ultrathin NiFe LDH active phase for industrial-level water oxidation - Yu Ma; Jia-Jun Wang; Xiao-Han Liu; Na Xu; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Are wearable local cooling devices effective in Chinese residential kitchens during hot summer? - Lumeng Liu; Jinghui Xin; Zhi Liu; Wenmao Zeng; Qisheng Li; Ling Jin; Ruoyu You; Meng Liu; Huan Liu (Building and Environment, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Somatic embryogenesis of slash pine (Pinus elliottii Engelm.): initiation, maturation, germination and mycorrhization of regenerated plantlets - Qi Fei; You-Mei Chen; Xin Ke; Jian-Ren Ye; Li-Hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Unraveling the chemosensory characteristics dependence of sauce-flavor baijiu on regionality using descriptive sensory analysis and quantitative targeted flavoromics - Xin Li; Busheng Zhang; Wenxuan Li; Yawen Zhao; Xiaotong Lyu; Xiaolong You; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Meta-analyzing the mechanism of pyrogenic biochar strengthens nitrogen removal performance in sulfur-driven autotrophic denitrification system: Evidence from metatranscriptomics - Wen-Jie Ma; Han-Min Zhang; Zi-Shang Ma; Xiu-Jia You; Xin-Yue Wei; Yue Li; Yu Tian (Water Research, 2024)

Two undescribed compounds from Silybum marianum and their cytotoxicity activities - Jing Wang; Juan Pan; Xin Meng; Zhi-Chao Hao; Jia-Tong Wu; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Yan Liu; Bing-You Yang (Phytochemistry Letters, 2024)

Fullerenol mitigates ischemia/reperfusion-induced kidney injury - Hao Wang; Junsong Guo; Xuefeng Ding; Ying Li; Hui Xu; Xinyi Tian; Xin Tan; You Liao; Haiyang Jiang; Jing Wei; Haijun Peng; Zhanjun Gu; et al. (Chemical Engineering Journal, 2024)

Ni-CaO-CaZrO3 bi-functional materials for high purity hydrogen production via sorption enhanced steam reforming of ethanol - Yinxiang Wang; Hui Zhou; Dingding Yao; Gianni Olguin; Haixia Ding; Boyu Qu; Wensheng Xie; Zegang Fu; You Guo; Xin Wang; Aimin Li; Guozhao Ji (Journal of Cleaner Production, 2024)

Efficient fabrication of cellulose nanofibers with novel superbase-derived ionic liquid/co-solvents: Rapid cellulose dissolution and improved solution electrospinnability - Xiaoyu Wang; Tingting You; Wenqiu Zheng; Xin Li; Sheng Chen; Feng Xu (Chemical Engineering Journal, 2024)

Contribution of anthropogenic emission changes to the evolution of PM2.5 concentrations and composition in the Pearl River Delta during the period of 2006–2020 - Jinlong Zhang; Yinyan Huang; Ning Zhou; Zhijiong Huang; Bowen Shi; Xin Yuan; Li Sheng; Andi Zhang; Yan You; Duohong Chen; Xiaofeng Huang; Junyu Zheng (Atmospheric Environment, 2024)

VX-765 Alleviates Circadian Rhythm Disorder in a Rodent Model of Traumatic Brain Injury Plus Hemorrhagic Shock and Resuscitation - Yan Li; Yue Xin; Man-Man Qi; Zhi-You Wu; Han Wang; Wei-Chao Zheng; Jie-Xia Wang; Dong-Xue Zhang; Li-Min Zhang (Journal of Neuroimmune Pharmacology, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Phase transformations and microstructure evolution of boron-containing iron concentrate during roasting under CO-CO2-N2 atmosphere: Synergistic effect of soda-ash and CO concentration - Jinxiang You; Meishi Hu; Mingjun Rao; Xin Zhang; Jun Luo; Zhiwei Peng; Guanghui Li (Minerals Engineering, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Arbuscular mycorrhizal symbiosis alleviates arsenic phytotoxicity in flooded Iris tectorum Maxim. dependent on arsenic exposure levels - Shuping Xing; Qihui Shen; Chuning Ji; Luhua You; Jinglong Li; Meng Wang; Guang Yang; Zhipeng Hao; Xin Zhang; Baodong Chen (Environmental Pollution, 2024)

FTase inhibitors and cancer: prospects for use in targeted therapies - Ming-tao Xia; Ling Yu; Zhi-wei Yan; You-de Wang; Li-ying Zhang; Guang-xin Miao; Shuai Li (Medicinal Chemistry Research, 2024)

Net greenhouse gas balance in U.S. croplands: How can soils be part of the climate solution? - Yongfa You; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; William D. Batchelor; Bo Cheng; Dafeng Hui; David Kicklighter; Xin‐Zhong Liang; Xiaoyong Li; Jerry Melillo; et al. (Global Change Biology, 2024)
Agricultural soils play a dual role in regulating the Earth's climate by releasing or sequestering carbon dioxide (CO 2 ) in soil organic carbon (SOC) and emitting non‐CO 2 greenhouse gases (GHGs) such as nitrous oxide (N 2 O) and methane (CH 4 ). To understand how agricultural soils can play a role in climate solutions requires a comprehensive assessment of net soil GHG balance (i.e., sum of SOC‐sequestered CO 2 and non‐CO 2 GHG emissions) and the underlying controls. Herein, we used a model‐data integration approach to understand and quantify how natural and anthropogenic factors have affected the magnitude and spatiotemporal variations of the net soil GHG balance in U.S. croplands during 1960–2018. Specifically, we used the dynamic land ecosystem model for regional simulations and used field observations of SOC sequestration rates and N 2 O and CH 4 emissions to calibrate, validate, and corroborate model simulations. Results show that U.S. agricultural soils sequestered Tg CO 2 ‐C year −1 in SOC (at a depth of 3.5 m) during 1960–2018 and emitted Tg N 2 O‐N year −1 and Tg CH 4 ‐C year −1 , respectively. Based on the GWP100 metric (global warming potential on a 100‐year time horizon), the estimated national net GHG emission rate from agricultural soils was Tg CO 2 ‐eq year −1 , with the largest contribution from N 2 O emissions. The sequestered SOC offset ~28% of the climate‐warming effects resulting from non‐CO 2 GHG emissions, and this offsetting effect increased over time. Increased nitrogen fertilizer use was the dominant factor contributing to the increase in net GHG emissions during 1960–2018, explaining ~47% of total changes. In contrast, reduced cropland area, the adoption of agricultural conservation practices (e.g., reduced tillage), and rising atmospheric CO 2 levels attenuated net GHG emissions from U.S. croplands. Improving management practices to mitigate N 2 O emissions represents the biggest opportunity for achieving net‐zero emissions in U.S. croplands. Our study highlights the importance of concurrently quantifying SOC‐sequestered CO 2 and non‐CO 2 GHG emissions for developing effective agricultural climate change mitigation measures.

Research progress on the application of different preservation methods for controlling fungi and toxins in fruit and vegetable - Yanli You; Yunna Zhou; Xuewu Duan; Xin Mao; Yanshen Li (Critical Reviews in Food Science and Nutrition, 2023)

Correlations between flavor and fermentation days and changes in quality-related physiochemical characteristics of fermented Aurantii Fructus - Ya-Ting Xie; Ting-Ting Bai; Tao Zhang; Peng Zheng; Min Huang; Li Xin; Wen-Hui Gong; Abid Naeem; Fang-You Chen; Hua Zhang; Jin-Lian Zhang (Food Chemistry, 2023)

In situ synthesis of bi-functional NH2-Ti2C3Tx@COF Schottky heterojunction through interfacial electron effects for enhancing U(VI) photoreduction - You-Gan Wang; Wei Jiang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

The impacts of clean energy policies on air pollutants and CO2 emission reduction in Shaanxi, China - Xin Bo; Qian You; Minjie Sang; Peng Wang; Shaobo Chen; Xin Xu; Wanyue Shan; Ying Yang; Bertrand Bessagnet; Hongmei Li; Yong Xiao (Atmospheric Pollution Research, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Differential interference of copper with endophytic bacterial inoculation: Atrazine decontamination in Acorus tatarinowii and culture solution - Xin Wang; Li Wang; Yongqiang You; Dongguang Yang; Yuqing Cao; Yujiao Wang; Fang Ma (Environmental Pollution, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)

Seasonal variations and drivers of energy fluxes and partitioning along an aridity gradient in temperate grasslands of Northern China - Yanbing Wang; Cuihai You; Yanhong Gao; Yuqiang Li; Yayi Niu; Changliang Shao; Xu Wang; Xiaoping Xin; Guirui Yu; Xingguo Han; Shiping Chen (Agricultural and Forest Meteorology, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

A sensitive single-layered graphene oxide-based sensor for electrochemical sensing of phosphate anion - Shuang-Ning Li; Ya You; Wei-Guo Hu; Guan-Jin Gao; Xin-Yu Jiang; Jin-Gang Yu (Process Safety and Environmental Protection, 2023)

Purification of soybean Kunitz trypsin inhibitor and the mechanism of its passivation by lysine and disulfide bond modifications - Xin Kong; You Li; Xinqi Liu (Food Bioscience, 2023)

Exploration of glycosyltransferases mutation status in cervical cancer reveals PARP14 as a potential prognostic marker - Hui Wang; Shen Luo; Xin Wu; Yuanyuan Ruan; Ling Qiu; Hao Feng; Shurong Zhu; Yanan You; Ming Li; Wenting Yang; Yanding Zhao; Xiang Tao; et al. (Glycoconjugate Journal, 2023)
This study investigates the potential role of Glycosyltransferases (GTs) in the glycosylation process and their association with malignant tumors. Specifically, the study focuses on PARP14, a member of GTs, and its potential as a target for tumors in the diagnosis and treatment of cervical cancer. To gather data, the study used somatic mutation data, gene expression data and clinical information from TCGA-CESE dataset as well as tissue samples from cervical cancer patients. Further verification was conducted through RT-qPCR and immunohistochemistry staining on cervical cancer tissues to confirm the expression of PARP14. The study utilized Kaplan-Meier for survival analysis of cervical cancer patient and found significant mutational abnormalities in GTs. The high frequency mutated gene was identified as PARP14. RT-qPCR revealed significantly higher mRNA expression of PARP14 compared to precancerous tissue. Using IHC combined with Kaplan-Meier,patients in the PARP14 high expression group had a better prognosis than the low expression group. The study identified PARP14 as a frequently mutated gene in cervical cancer and proposed its potential role in diagnosis and treatment.

Screening and prioritization of organic chemicals in a large river basin by suspect and non-target analysis - Jia-Hui Zhao; Li-Xin Hu; Sheng Xiao; Jian-Liang Zhao; You-Sheng Liu; Bin Yang; Qian-Qian Zhang; Guang-Guo Ying (Environmental Pollution, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Optimized high-order finite-difference modeling of second-order strain gradient wave field effects - Zi-hao Hu; Hai-xin Feng; Zhi-chun Zhou; You-ming Li; Zhi-yang Wang (Applied Geophysics, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Challenges and engineering application of landfill leachate concentrate treatment - Qian Li; Hanlin Cui; Yihao Li; Xin Song; Wenzong Liu; Yongxuan Wang; Haimeng Hou; Hongbo Zhang; You Li; Fan Wang; Jun Song; Hanfeng Ye; et al. (Environmental Research, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Wheat straw pyrochar more efficiently decreased enantioselective uptake of dinotefuran by lettuce and dissemination of antibiotic resistance genes than hydrochar in an agricultural soil - Yadong Cheng; Xiao Wang; Liuwei Zhao; Xin Zhang; Qingxian Kong; Hui Li; Xiangwei You; Yiqiang Li (Science of The Total Environment, 2023)

Ultrasonic-assisted self-assembly of a neodymium vanadate and hydroxylated multi-walled carbon nanotubes composite for electrochemical detection of p-nitrophenol - Ya You; Shuang-Ning Li; Jiao Zou; Ya-Nan Xin; Sui Peng; Bo Liu; Xin-Yu Jiang; Jin-Gang Yu (Process Safety and Environmental Protection, 2023)

Enhanced electromagnetic wave absorption, thermal conductivity and flame retardancy of BCN@LDH/EP for advanced electronic packing materials - Yongxin Qian; Yubo Luo; You Li; Tianshun Xiong; Luyao Wang; Wenguang Zhang; Shuangfu Gang; Xin Li; Qinghui Jiang; Junyou Yang (Chemical Engineering Journal, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

How does phosphorus influence Cd tolerance strategy in arbuscular mycorrhizal - Phragmites australis symbiotic system? - Yongqiang You; Li Wang; Chang Ju; Xin Wang; Yujiao Wang (Journal of Hazardous Materials, 2023)

Development of an efficient insecticide substrate and inhibitor screening system of insect P450s using fission yeast - Xiang Li; Lianyun Lin; Zhi Li; Hadiatullah Hadiatullah; Shishir Sharma; He Du; Xin Yang; Wei Chen; Shijun You; Matthias Bureik; Zhiguang Yuchi (Insect Biochemistry and Molecular Biology, 2023)

Cyano-functionalized ionic porous polymer: A novel adsorbent for effectively enriching trace estrogens in water and milk - Zixuan Cai; Xin Zhou; Yushi Yang; Jie Li; Weihua Liu; Qianqian Wang; Lin Hao; Zhi Wang; Yusuke Yamauchi; Jungmok You; Shuaihua Zhang; Qiuhua Wu; et al. (Chemical Engineering Journal, 2023)

Metformin Alleviates Delayed Hydrocephalus after Intraventricular Hemorrhage by Inhibiting Inflammation and Fibrosis - Yi Cao; Chang Liu; Gaowei Li; Weina Gao; Hui Tang; Shuanmin Fan; Xin Tang; Long Zhao; Haoxiang Wang; Aijun Peng; Chao You; Aiping Tong; et al. (Translational Stroke Research, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Combining mechanisms of black carbon and magnetic minerals in power plant fly ash - Meng Yao Li; Zhou Xin Peng; You Ying Chen; Shi Yun Xiao; Bo Wen Zhang; Yi Xin Shen; Sheng Kang Wang; Xue Song Wang; Zhao Xiang Han (Science of The Total Environment, 2023)

Diversity of Wolbachia infection and its influence on mitochondrial DNA variation in the diamondback moth, Plutella xylostella - Xiangyu Zhu; Tiansheng Liu; Ao He; Ling Zhang; Jinyang Li; Tianpu Li; Xin Miao; Minsheng You; Shijun You (Molecular Phylogenetics and Evolution, 2023)

New insights into in mycotoxins production in Alternaria infected apple during postharvest storage - Xin Mao; Anqi Chen; Jingyao Qu; Pengjie Luo; Yanli You; Yonglin Gao; Fengguang Dong; Yongning Wu; Yanshen Li (Postharvest Biology and Technology, 2023)

Vertically aligned Ag-decorated MoS2 nanosheets supported on polyvinyl alcohol flexible substrate enable high-sensitivity and self-cleaning SERS devices - Xinyue Song; Xiaofei You; Xiaohui Ren; Xuelin Zhang; Dongyan Tang; Xin Li (Journal of Environmental Chemical Engineering, 2023)

Deciphering the fate of osmotic stress priming on enhanced microorganism acclimation for purified terephthalic acid wastewater treatment with high salinity and organic load - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Bioresource Technology, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Impacts of PFOAC8, GenXC6, and their mixtures on zebrafish developmental toxicity and gene expression provide insight about tumor-related disease - Huinian Liu; Yu Chen; Wenli Hu; Yuan Luo; Ping Zhu; Shiqi You; Yunxuan Li; Zhaobiao Jiang; Xiushan Wu; Xin Li (Science of The Total Environment, 2023)

Hydrochar more effectively mitigated nitrous oxide emissions than pyrochar from a coastal soil of the Yellow River Delta, China - Xiangwei You; Xiao Wang; Ruixue Sun; Qiang Liu; Song Fang; Qingxian Kong; Xin Zhang; Chenghao Xie; Hao Zheng; Hui Li; Yiqiang Li (Science of The Total Environment, 2023)

Temperature-regulated and starvation-induced refractory para-toluic acid anaerobic biotransformation - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Chemosphere, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

Process analysis of asymmetric interaction between copper and atrazine in a system of macrophytes - Xin Wang; Weiming Wang; Li Wang; Gen Wang; Yongqiang You; Fang Ma (Science of The Total Environment, 2023)

Screening of structural and functional alterations in duckweed (Lemna minor) induced by per- and polyfluoroalkyl substances (PFASs) with FTIR spectroscopy - Ying-Lin Wu; Qian Xiong; Ben Wang; You-Sheng Liu; Pei-Liang Zhou; Li-Xin Hu; Fang Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Compensation strategy for constructing high-performance aerogels using acrylamide-assisted vacuum drying and their use as water-induced electrical generators - Juncheng Fan; Hengrui Li; Songsong Tang; Boxiao Li; Yangyang Xin; You-Lo Hsieh; Jian Zhou (Chemical Engineering Journal, 2023)

High-efficiency luminescent solar concentrators based on Composition-tunable Eco-friendly Core/shell quantum dots - Yimin You; Xin Tong; Ali Imran Channa; Huaqian Zhi; Mengke Cai; Hongyang Zhao; Li Xia; Guiju Liu; Haiguang Zhao; Zhiming Wang (Chemical Engineering Journal, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Activation of the STING pathway induces peripheral sensitization via neuroinflammation in a rat model of bone cancer pain - Yuxin Zhang; Wei Wang; Zhihao Gong; Yuan Peng; Xin Li; Zuojing Zhang; Xiaoxuan Zhang; Xingji You; Jingxiang Wu (Inflammation Research, 2023)
Background Neuroinflammation in the peripheral nervous system has been linked to cancer metastasis-induced bone pain. The stimulator of interferon genes (STING), an innate immune sensor for cytosolic DNA, plays an important role in inflammation and cancer metastasis and is reported to be a critical regulator of nociception. Here, we examined the role of STING in primary nociceptive neurons and chronic pain to determine if it could be a new target for treating bone cancer pain (BCP). Methods Walker 256 cancer cells were injected intratibially to induce bone cancer pain in rats. STING and its downstream inflammatory factors in dorsal root ganglia (DRG) were detected using western blotting and immunofluorescent staining. Transmission electron microscopy and the BCL2-associated X (Bax) expression were used to detect the mitochondrial stress in DRG neurons. C-176, a specific inhibitor of STING, was used to block STING activation and to test the pain behavior. Results Mechanical hyperalgesia and spontaneous pain were observed in BCP rats, accompanied by the upregulation of the STING expression in the ipsilateral L4-5 DRG neurons which showed significant mitochondrion stress. The STING/TANK-binding kinase 1 (TBK1)/nuclear factor-kappa B (NF-κB) pathway activation was observed in the DRGs of BCP rats as well as increased IL-1β, IL-6, and TNF-α expression. C-176 alleviated bone cancer pain and reduced the STING and its downstream inflammatory pathway. Conclusion We provide evidence that STING pathway activation leads to neuroinflammation and peripheral sensitization. Pharmacological blockade of STING may be a promising novel strategy for preventing BCP.

First Detection and Molecular Identification of Entamoeba bovis in Farm-Raised Sika Deer from Anhui Province, China - Xin-chao Liu; Qi Ren; Jie Guo; Dong-qian Chen; Qiao-qiao Li; Xin-yu Luo; You-fang Gu; Wen-chao Li (Acta Parasitologica, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Functional differentiation and complementation of alkaline phosphatases and choreography of DOP scavenging in a marine diatom - Kaidian Zhang; Jiashun Li; Jierui Wang; Xin Lin; Ling Li; Yanchun You; Xiaomei Wu; Zhi Zhou; Senjie Lin (Molecular Ecology, 2022)
Facing phosphate deficiency, phytoplankton use alkaline phosphatase (AP) to scavenge dissolved organophosphate (DOP). AP is a multitype (e.g., PhoA, PhoD) family of hydrolases and is known as a promiscuous enzyme with broad DOP substrate compatibility. Yet, whether the multiple types differentiate on substrates and collaborate to provide physiological flexibility remain elusive. Here we identify PhoA and PhoDs and document the functional differentiation between PhoA and a PhoD (PhoD_45757) in Phaeodactylum tricornutum . CRISPR/Cas9‐based mutations and physiological analyses reveal that (1) PhoA is a secreted enzyme and contributes the majority of total AP activity whereas PhoD_45757 is intracellular and contributes a minor fraction of the total AP activity, (2) AP gene expression compensates for each other after one is disrupted, (3) the DOP→PhoA→phosphate_uptake and the DOP_uptake→PhoD→phosphate pathways function interchangeably for some DOP substrates. These findings shed light on the underpinning of AP’s multiformity and have important implications in phytoplankton phosphorus‐nutrient niche differentiation, physiological plasticity, and competitive strategy.

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Geochemical characteristics and source of crude oil in the Shenhu uplift, Pearl River Mouth Basin, South China Sea - Xiaoyan Fu; Shijia Chen; Xin He; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Two new alkaloids from the sepals of Solanum melongena L - Dong-Ying Zhao; Yan Liu; Xin Yin; Xiao-Mao Li; Juan Pan; Wei Guan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2021)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Somatic embryogenesis of masson pine (Pinus massoniana): initiation, maturation and genetic stability analysis at SSR loci - Xin-Rui Xia; Fan Yang; Xin Ke; You-Mei Chen; Jian-Ren Ye; Li-Hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Phenotypic characterization of the glossy1 mutant and fine mapping of GLOSSY1 in common wheat (Triticum aestivum L.) - Linghong Li; Lingling Chai; Huanwen Xu; Huijie Zhai; Tianya Wang; Mingyi Zhang; Mingshan You; Huiru Peng; Yingyin Yao; Zhaorong Hu; Mingming Xin; Weilong Guo; et al. (Theoretical and Applied Genetics, 2021)

Hypoxia/reoxygenation-induced upregulation of miRNA-542-5p aggravated cardiomyocyte injury by repressing autophagy - Fei Wang; Xin Min; Shan-you Hu; Da-li You; Ting-ting Jiang; Li Wang; Xiao Wu (Human Cell, 2021)

Application of DGT/DIFS combined with BCR to assess the mobility and release risk of heavy metals in the sediments of Nansi Lake, China - Min Zhang; Cai Li; Liyuan Yang; Shiming Ding; Xin Ma; You Zhang; Tingting Zhao (Environmental Geochemistry and Health, 2020)

2(5H)-Furanone Disrupts Bacterial Biofilm Formation and Indirectly Reduces the Settlement of Plantigrades of the Mussel Mytilus coruscus - Yi-Feng Li; Xin Zhu; Zhi-Yang Cheng; Xiao Liang; You-Ting Zhu; Dan-Dan Feng; Sergey Dobretsov; Jin-Long Yang (Frontiers in Marine Science, 2020)

A new epicatechin glucopyranoside derivative from Styrax suberifolius - Bing-Lei Liu; Xin Hu; Hua-Liang He; Lin Qiu; You-Zhi Li; Wen-Bing Ding (Natural Product Research, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

The semidominant mutation w5 impairs epicuticular wax deposition in common wheat (Triticum aestivum L.) - Linghong Li; Zhongqi Qi; Lingling Chai; Zhaoyan Chen; Tianya Wang; Mingyi Zhang; Mingshan You; Huiru Peng; Yingyin Yao; Zhaorong Hu; Mingming Xin; Weilong Guo; et al. (Theoretical and Applied Genetics, 2020)

Selenate Reduction and Selenium Enrichment of Tea by the Endophytic Herbaspirillum sp. Strain WT00C - Xiao Xu; Wei Cheng; Xin Liu; Heng You; Guitai Wu; Kunming Ding; Xiuliang Tu; Lanfang Yang; Youpin Wang; Yadong Li; Haoshuang Gu; Xingguo Wang (Current Microbiology, 2020)

Reef-carbonate diagenesis in the Pleistocene–Holocene of the well Xike#1, Xisha Islands, South China Sea: implications on sea-level changes - Na Liu; Zhen-feng Wang; Xu-shen Li; Li Liu; Dao-jun Zhang; Li You; Wei Luo; Xin-yu Liu (Carbonates and Evaporites, 2019)

Spatial distribution patterns of rock fragments and their underlying mechanism of migration on steep hillslopes in a karst region of Yunnan Province, China - Juan Liu; You-xin Shen; Xi-ai Zhu; Gao-juan Zhao; Zhi-meng Zhao; Zhen-jiang Li (Environmental Science and Pollution Research, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Concurrent droughts and hot extremes in northwest China from 1961 to 2017 - Xin Li; Qinglong You; Guoyu Ren; Suyan Wang; Yuqing Zhang; Jianling Yang; Guangfen Zheng (International Journal of Climatology, 2019)
Northwest China forms the main part of the arid and semiarid areas in China, and even includes some extremely arid areas. This zone of interaction is affected by the westerlies and monsoons making it sensitive to global climate change. Drought is the main type of natural disaster affecting northwest China. Global warming has caused a gradual strengthening of the frequency and intensity of hot extremes, when dry conditions and heatwaves occur simultaneously or successively; as a result, that socioeconomic risks can increase considerably. The present study examined changes in concurrent droughts and hot extremes in northwest China during 1961–2017 based on data from 119 meteorological stations. The result shows that the frequency of concurrent droughts and hot extremes exhibited an increasing trend over most parts of northwest China, while a negative trend occurred in western Xinjiang and at some sites in Qinghai. Concurrent droughts and hot extremes appeared more often in May in western Xinjiang, and in summer in other parts of northwest China. Overall, the trends of such concurrent events, regardless of different definitions, increased from 1961–2017 over northwest China. In particular, from 1981–2017, the trend rose more significantly than in other decades, and reached an abrupt point of change in 1996. Although the trend changed from a positive significant signal to a negative one from 2001–2017, the trend grew 2–3 times from 1997–2017. Changes in large‐scale atmospheric circulation show that an anticyclonic circulation strengthened, increasing in geopotential height over the midhigh latitudes of Eurasia and was centred on Mongolia and Lake Baikal. This enhanced relative humidity in western Xinjiang and eastern Qinghai, and weakened it elsewhere from 1997–2017. These changes have contributed to the changes in the spatial distribution and trends in concurrent droughts and hot extremes in northwest China.

OsDCL3b affects grain yield and quality in rice - Peng-Fei Liao; Jie-Xiu Ouyang; Jian-Jun Zhang; Lan Yang; Xin Wang; Xiao-Jue Peng; Dong Wang; You-Lin Zhu; Shao-Bo Li (Plant Molecular Biology, 2019)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Transcription profiling and identification of infection-related genes in Phytophthora cactorum - Xiao-Ren Chen; Shen-Xin Huang; Ye Zhang; Gui-Lin Sheng; Bo-Yue Zhang; Qi-Yuan Li; Feng Zhu; Jing-You Xu (Molecular Genetics and Genomics, 2018)

Assessment of prospective hazards resulting from the 2017 earthquake at the world heritage site Jiuzhaigou Valley, Sichuan, China - Xiao-qing Chen; Jian-gang Chen; Peng Cui; Yong You; Kai-heng Hu; Zong-ji Yang; Wei-feng Zhang; Xin-po Li; Yong Wu (Journal of Mountain Science, 2018)

Behaviors of Organic and Heavy Metallic Pollutants during Supercritical Water Oxidation of Oil-Based Drill Cuttings - Guanghua Yao; Zhong Chen; Qiao Chen; Dongyuan Li; Zhiguo Xie; You Zhou; Xin Xiong; Yuanjian Xu (Water, Air, & Soil Pollution, 2018)

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata - Chuan-Wen Lei; Zhi-Qin Yang; Yan-Ping Zeng; Yun Zhou; Yi Huang; Xin-Sheng He; Guo-You Li; Xiao-Hong Yuan (Natural Product Research, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Cloning and elucidation of the functional role of apple MdLBD13 in anthocyanin biosynthesis and nitrate assimilation - Hao-Hao Li; Xin Liu; Jian-Ping An; Yu-Jin Hao; Xiao-Fei Wang; Chun-Xiang You (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Association Between Plasminogen Activator Inhibitor-1 Genetic Polymorphisms and Stroke Susceptibility - Xin Hu; Xin Zan; Zhiyi Xie; Yunke Li; Sen Lin; Hao Li; Chao You (Molecular Neurobiology, 2017)

Evaluation of estrogenic activity in the Pearl River by using effect-directed analysis - Xiao -Wen Chen; Jian-Liang Zhao; You-Sheng Liu; Li-Xin Hu; Shuang-Shuang Liu; Guang-Guo Ying (Environmental Science and Pollution Research, 2016)

Tight regulation of the interaction between Brassica napus and Sclerotinia sclerotiorum at the microRNA level - Jia-Yi Cao; You-Ping Xu; Li Zhao; Shuang-Sheng Li; Xin-Zhong Cai (Plant Molecular Biology, 2016)

Rock outcrops redistribute water to nearby soil patches in karst landscapes - Dian-jie Wang; You-xin Shen; Jin Huang; Yu-hui Li (Environmental Science and Pollution Research, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Rat Liver Mitochondrial Dysfunction Induced by an Organic Arsenical Compound 4-(2-Nitrobenzaliminyl) Phenyl Arsenoxide - Yuan-Hong Jiao; Qian Zhang; Ling-Li Pan; Xin-You Chen; Ke-Lin Lei; Jie Zhao; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2015)

Hydrogen peroxide is indispensable to Xanthomonas oryzae pv. oryzae-induced hypersensitive response and nonhost resistance in Nicotiana benthamiana - Wen Li; You-Ping Xu; Juan Yang; Gong-You Chen; Xin-Zhong Cai (Australasian Plant Pathology, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Early channel transurethral resection of the prostate for patients with urinary retention after brachytherapy - You-yun Zhang; Zhi-gen Zhang; Yan-lan Yu; Yi-cheng Chen; Kang-xin Ni; Ming-chao Wang; Wei-ping Zhao; Faisal Rehman; Shaw P. Wan; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2014)

Distribution, geochemistry and age of the Millennium eruptives of Changbaishan volcano, Northeast China — A review - Chunqing Sun; Haitao You; Jiaqi Liu; Xin Li; Jinliang Gao; Shuangshuang Chen (Frontiers of Earth Science, 2014)

Distribution, geochemistry and age of the Millennium eruptives of Changbaishan volcano, Northeast China — A review - Chunqing Sun; Haitao You; Jiaqi Liu; Xin Li; Jinliang Gao; Shuangshuang Chen (Frontiers of Earth Science, 2014)

Cloning and in silico analysis of a cinnamyl alcohol dehydrogenase gene in Pennisetum purpureum - RAN TANG; XIANG-QIAN ZHANG; YOU-HAN LI; XIN-MING XIE (Journal of Genetics, 2014)

Cysteine residues 87 and 320 in the amino terminal domain of NMDA receptor GluN2A govern its homodimerization but do not influence GluN2A/GluN1 heteromeric assembly - Xiao-Min Zhang; Xin-You Lv; Yang Tang; Li-Jun Zhu; Jian-Hong Luo (Neuroscience Bulletin, 2013)

Bacillus oceani sp. nov., a new slightly halophilic bacterium, isolated from a deep sea sediment environment - Yu-Juan Liu; Li-Juan Long; Xiao-Fang Huang; Zhi-Qing You; Fa-Zuo Wang; Jie Li; Chang-Jin Kim; Xin-Peng Tian; Si Zhang (Antonie van Leeuwenhoek, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Bacillus abyssalis sp. nov., isolated from a sediment of the South China Sea - Zhi-Qing You; Jie Li; Sheng Qin; Xin-Peng Tian; Fa-Zuo Wang; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Molecular cloning and functional characterization of MdSOS2 reveals its involvement in salt tolerance in apple callus and Arabidopsis - Da-Gang Hu; Ming Li; Hua Luo; Qing-Long Dong; Yu-Xin Yao; Chun-Xiang You; Yu-Jin Hao (Plant Cell Reports, 2012)

Quantitative Analysis of Quercetin in Euphorbia helioscopia L by RP-HPLC - Hai Peng Liu; Xiao Feng Shi; You Cheng Zhang; Zhong Xin Li; Lin Zhang; Zhe Yuan Wang (Cell Biochemistry and Biophysics, 2011)

N-palmitoylethanolamide derivatives: synthesis and studies on anticonvulsant and antidepressant activities - Li-Ping Guan; Xin Sui; Xian-Qing Deng; Dong-Hai Zhao; You-Le Qu; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

The soybean GmbZIP1 transcription factor enhances multiple abiotic stress tolerances in transgenic plants - Shi-Qing Gao; Ming Chen; Zhao-Shi Xu; Chang-Ping Zhao; Liancheng Li; Hui-jun Xu; Yi-miao Tang; Xin Zhao; You-Zhi Ma (Plant Molecular Biology, 2011)

Minimally-invasive treatment of communicating hydrocephalus using a percutaneous lumboperitoneal shunt - Lu Jia; Zhong-xin Zhao; Chao You; Jia-gang Liu; Si-qing Huang; Min He; Pei-gang Ji; Jie Duan; Yi-jun Zeng; Guo-ping Li (Journal of Zhejiang University-SCIENCE B, 2011)

Metachronous contralateral testicular and bilateral adrenal metastasis of chromophobe renal cell carcinoma: a case report and review of the literature - Hai-yang Wu; Li-wei Xu; You-yun Zhang; Yan-lan Yu; Xin-de Li; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2010)

Ischemic compression block attenuates mechanical hyperalgesia evoked from latent myofascial trigger points - Yong-Hui Wang; Xin-Li Ding; Yang Zhang; Jing Chen; Hong-You Ge; Lars Arendt-Nielsen; Shou-Wei Yue (Experimental Brain Research, 2010)

A system for screening agonists targeting β2-adrenoceptor from chinese medicinal herbs - Hui Wang; Shi-you Li; Chuan-ke Zhao; Xin Zeng (Journal of Zhejiang University-SCIENCE B, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Changes in nitrogen resorption traits of six temperate grassland species along a multi-level N addition gradient - Ju-Ying Huang; Xiao-Guang Zhu; Zhi-You Yuan; Shi-Huan Song; Xin Li; Ling-Hao Li (Plant and Soil, 2008)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

Molecular relationships between type Asia 1 new strain from China and type O Panasia strains of foot-and-mouth-disease virus - Dong Li; You-Jun Shang; Zai-Xin Liu; Xiang-Tao Liu; Xue-Peng Cai (Virus Genes, 2007)

Frequent loss of membranous E-cadherin in gastric cancers: A cross-talk with Wnt in determining the fate of β-catenin - Xiao-Xin Cheng; Zi-Chuang Wang; Xiao-Yan Chen; Yuan Sun; Qing-You Kong; Jia Liu; Xue Gao; Hong-Wei Guan; Hong Li (Clinical & Experimental Metastasis, 2005)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)